The influence of urban form on car travel following residential relocation: a current and retrospective study in Scottish urban areas - Woods, Lee; Ferguson, Neil (Journal of Transport and Land Use, 2014)
Spatial planning and policy continues to be used as a tool to bring about changes in travel behavior. Policy suggests that by creating particular urban forms, demand for travel by car can be reduced. This paper uses data collected in 2006 from 280 households in Glasgow and Edinburgh to analyze the relationships between urban form and vehicle miles driven, with an emphasis on those who had recently relocated. Population densities, housing type, distance to urban center, and measures of mix were collected for the current residential location and prior residence for those who had relocated in the previous three years. An ordinal regression model of change in urban form showed significant associations with reported change in miles driven, although the effect was small compared with the effects of socioeconomic factors and car ownership. While the results give some weight to intensification as a policy to bring about a reduction in average distance driven, there may be an increase in total distance driven in the intensified area with a corresponding increase in congestion. Whether such intensification can be enacted against a backdrop of preferences toward suburban, car-oriented living is contentious. As such, this study calls into question the use of planning policy as a means to reduce car use in Scottish cities.